An LMI Approach to Full- and Reduced-Order Switched Luenberger Observers for Switched Affine Systems - Yoshimura, Victor Leonardo; Assunção, Edvaldo [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP] (Springer Nature, 2016)
This work deals with reduced-order Luenberger-like observer design and control for switched affine systems. Formulation of state-dependent and dynamic output-dependent switching laws for those systems was already addressed, however, in a full-order treatment. The proposed procedure defines an estimator system only for the unmeasured part of the system state. Linear matrix inequalities for obtaining output gain matrices and for composing a reduced-order Luenberger observer-based switching law are proposed. Finally, the results are validated by design and simulation for DC–DC converters.
Keywords: DC–DC converters; Linear matrix inequalities; Reduced order switched Luenberger observers; Switched affine systems; Switched Luenberger observers